Elements of musical and dance sophistication predict musical groove perception - O’Connell, Samantha R.; Nave-Blodgett, Jessica E.; Wilson, Grace E.; Hannon, Erin E.; Snyder, Joel S. (Frontiers in Psychology, 2022)
Listening to groovy music is an enjoyable experience and a common human behavior in some cultures. Specifically, many listeners agree that songs they find to be more familiar and pleasurable are more likely to induce the experience of musical groove. While the pleasurable and dance-inducing effects of musical groove are omnipresent, we know less about how subjective feelings towards music, individual musical or dance experiences, or more objective musical perception abilities are correlated with the way we experience groove. Therefore, the present study aimed to evaluate how musical and dance sophistication relates to musical groove perception. One-hundred and twenty-four participants completed an online study during which they rated 20 songs, considered high or low groove, and completed the Goldsmiths Musical Sophistication Index, the Goldsmiths Dance Sophistication Index, the Beat and Meter Sensitivity Task, and a modified short version of the Profile for Music Perception Skills. Our results reveal that perceptual abilities, musical training, and social dancing predicted the difference in groove rating between high- and low-groove music. Overall, these findings support the notion that listeners’ individual experiences and predispositions may shape their perception of musical groove, although other causal directions are also possible. This research helps elucidate the correlates and possible causes of musical groove perception in a wide range of listeners.